Correlation between Limb Muscle Exploitative Strength to Futsal Shooting Ability - Mokhamad Parmadi; Sekar Ayu Wigunani; Agus Setia Budi; Wisnu Murtiansyah; Ari Susanto (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This study aims to determine the relationship between the explosive power of leg muscles and the ability to shoot futsal. This research is a quantitative study with a correlational type. The sample in this study was 30 members of the Ababil futsal club. The instrument used in this study is a test of limb muscle exploitative strength and futsal shooting ability. The analysis techniques used are quantified statistics accompanied by hypothesis testing. Conclusions from the research findings are that there is a very meaningful relationship between the explosive power of the limb muscles and the shooting ability. Supporting data in addition to correlation, also found that the average explosive power of the player's limb muscles is 80, which reduces the average obtained player at the time of the ability test shooting in futsal games is 7.4. The results of this study have implications for paying special attention to athletes, especially the explosive power of the leg muscles because they contribute to the ability to shoot futsal. Special attention can be the program Exercises for the increased explosive power of limb muscles varied in certain Exercises. It is recommended for coaches and futsal coaches to pay attention to the elements of the explosive power of limb muscles in improving the ability to shoot in the game of futsal. It is expected in other studies to be able to see several other factors that have not been considered in this study. Keywords: leg muscle, explosive power, shooting, futsal